2018
DOI: 10.1007/s12134-018-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Youth and Their Challenge to Promote a Fairer Multicultural Society: a Qualitative Study of African Immigrant Activists

Abstract: Immigrants' activism in associations has been identified as a stepping stone for their integration within a new society (Handy and Greenspan, Nonprofit Volunt Sect Q 38:956-982, 2009). Within a liberation psychology perspective (LP) (García-Ramírez et al., Am J Community Psychol 47:86-97, 2011), the present study explores how being active in a national association (NA) or ethnic association (EA) can promote the integration of immigrants in social service associations. Sixteen interviews were conducted with y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
16
1
Order By: Relevance
“…Developing relationships could therefore have been a motivation for young migrants to continue their engagement. Studies have pointed out that social support in the host country promotes the integration of migrants (Gurak & Caces, 1992;Marzana et al, 2016;Marzana, Martinez Damia, Alfieri, & Marta, 2019;Palloni, Massey, Ceballos, Espinosa, & Spittel, 2001) as it helps them rebuild their social networks, usually lost after leaving their countries (Morrison, Laughlin, San Miguel, Smith, & Widaman, 1997;Schwarzer, Hahn, & Schröder, 1994;Vega, Kolody, Valle, & Weir, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Developing relationships could therefore have been a motivation for young migrants to continue their engagement. Studies have pointed out that social support in the host country promotes the integration of migrants (Gurak & Caces, 1992;Marzana et al, 2016;Marzana, Martinez Damia, Alfieri, & Marta, 2019;Palloni, Massey, Ceballos, Espinosa, & Spittel, 2001) as it helps them rebuild their social networks, usually lost after leaving their countries (Morrison, Laughlin, San Miguel, Smith, & Widaman, 1997;Schwarzer, Hahn, & Schröder, 1994;Vega, Kolody, Valle, & Weir, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The objective of their volunteering was to enhance the positive contribution that new cultures can give to Italy. This goes in the direction of building a multicultural society as other studies have shown (Marzana, Martinez Damia, Alfieri, & Marta, 2019).…”
Section: The Understanding Of My Religion […] Is a Journey That I Am mentioning
confidence: 88%
See 1 more Smart Citation
“…To navigate the cultural difference, newcomer youth and their families should be encouraged to take part in activities and events that bring youth from multicultural neighbourhoods together. Such activities could include taking part in ethnocultural and national activism organizations [ 47 ]. Service providers could also place emphasis in promoting cultural awareness between newcomer and non-newcomer youth to promote better navigation between cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Immigrant participation within their communities has been conceived of as a powerful tool in fostering immigrants' well-being (Alfieri, Marzana, & Cipresso, 2019;Handy & Greenspan, 2009;Marzana, Alfieri, & Marta, 2016;Paloma, Garc ıa-Ram ırez, & Camacho, 2014;Paloma, Garc ıa-Ram ırez, de la Mata, & Amal, 2010;Sung, Chin, Lee, & Lee, 2013) and resilience (Marzana, Martinez Damia, Atallah, & Martinez, 2019). Specifically, participation can be a way to create multicultural contexts that pursue or enhance social justice (Marzana, Martinez Damia, Alfieri, & Marta, 2019).…”
Section: Introductionmentioning
confidence: 99%